Spread of multidrug-resistant Enterococcus to animals and humans: an underestimated role for the pig farm environment - Carla Novais (2013)
Objectives: The aim of this study was to discover the potential role of the pig farm environment in the spread of multidrug-resistant (MDR) Enterococcus strains, including high-risk clones, to animals and humans. Methods: Enterococcus isolates were recovered from a variety of samples (n = 82; swine, feed/medicines/antiseptics and pig farm facilities) from six Portuguese farms, most using antibiotics. Antimicrobial susceptibility/conjugation assays were performed by standard procedures, bacterial identification/screening of antibiotic resistance genes were performed by PCR and clonality was determined using PFGE/multilocus sequence typing. Results: Enterococcus isolates resistant to antibiotics (n = 473) were recovered from samples of different origin (swine, feed/antiseptics, animal residues and pig farm facilities), but only the clinically relevant species Enterococcus faecium (n = 171) and Enterococcus faecalis (n = 78) were included for further comprehensive molecular analysis. Isolates resistant to vancomycin, ampicillin, tetracyclines, erythromycin and aminoglycosides were better recovered in Slanetz-Bartley medium with these antibiotics present than in media not supplemented with antibiotics (P < 0.05). E. faecium was more frequently resistant to ampicillin, ciprofloxacin or nitrofurantoin and E. faecalis to tetracyclines, chloramphenicol or aminoglycosides (P < 0.05). Glycopeptide and erythromycin resistance rates were similar in both species. The transfer of resistance to several antibiotics, including vancomycin and ampicillin, was demonstrated. Clones associated with human infections were detected in different samples from the same farm [E. faecium from sequence type (ST) 78 lineage and E. faecalis ST16; manure, waste lagoons, faeces and drinking water] and in geographically distant farms [E. faecium clonal complex (CC) 5; E. faecalis CC21 and ST16]. Conclusions: The pig farm environment has an underestimated potential role in the transmission of MDR Enterococcus to animals and, possibly, to humans. The continuous contact of swine with MDR Enterococcus by different routes (e. g. feed, dust, air and rooms) might decrease the impact of restrictive antibiotic use policies and reinforces the need for different and preliminary interventions at the husbandry management level.